Software development for evaporation estimation - Sobri Harun, author; University of London (London : Imperial College of Science and Technology, 1990)
An increasingly popular approach to the estimation of evapotranspiration is a set of methods developed by the United Nations Food and Agriculture Organization (FAO) and described by Doorenbos and Pruitt (1977). In this study versions of the Penman and Penman-Monteith equations developed at the Institute of Hydrology, Wallingford are compared to the FAO methods using automatic weather station data from Silwood Park. Sensitivity analysis is applied to the methods and in the Walling-ford versions the Penman equation has been tested for differences in the saturated water vapour-temperature expression latent heat and wind function equations. The results from thee Penman-Monteith equation in the Wallingford versions using a constant value of aerodynamic resistance are compared againts those using a variation in the wind speed and height of crop. The importance of the time interval for computation of the instaneous evapotranspiration is investigated. For short green grass in particular, the Penman-Monteith equation in the Wallingford versions yields similar results to the FAO Modified Penman for monthly average estimation.